ITScan: a web-based analysis tool for Internal Transcribed Spacer (ITS) sequences - Ferro, Milene [UNESP]; Antonio, Erik A.; Souza, Wélliton [UNESP]; Bacci, Maurício [UNESP] (BioMed Central, 2014)
Studies on fungal diversity and ecology aim to identify fungi and to investigate their interactions with each other and with the environment. DNA sequence-based tools are essential for these studies because they can speed up the identification process and access greater fungal diversity than traditional methods. The nucleotide sequence encoding for the internal transcribed spacer (ITS) of the nuclear ribosomal RNA has recently been proposed as a standard marker for molecular identification of fungi and evaluation of fungal diversity. However, the analysis of large sets of ITS sequences involves many programs and steps, which makes this task intensive and laborious. We developed the web-based pipeline ITScan, which automates the analysis of fungal ITS sequences generated either by Sanger or Next Generation Sequencing (NGS) platforms. Validation was performed using datasets containing ca. 2,000 to 40,000 sequences each. ITScan is an online and user-friendly automated pipeline for fungal diversity analysis and identification based on ITS sequences. It speeds up a process which would otherwise be repetitive and time-consuming for users. The ITScan tool and documentation are available at http://evol.rc.unesp.br:8083/itscan.
Keywords: Fungal biodiversity; Mycology; Pipeline; Web service